2015
DOI: 10.1007/s12011-015-0240-8
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in the Wall of Abdominal Aortic Aneurysms With and Without Coexisting Iliac Artery Aneurysms

Abstract: Iliac artery aneurysms (IAA) and abdominal aortic aneurysms (AAA) frequently coexist. It remains unknown whether the content of trace elements in AAA walls depends on the coexistence of IAAs. The aim of this study was to compare the content of selected trace elements in AAA walls depending on the coexistence of IAAs. The content of trace elements was assessed in samples of AAA walls harvested intraoperatively in 19 consecutive patients. In the studied group, coexisting IAAs were diagnosed in 11 out of the 19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Additionally, we found disturbed proportions between Cu and Pb in TAA and Zn and Pb in both types of aneurysm, while concentration of Cd is similar to normal aortas in both types of aneurysm. Other studies have shown that the elevated levels of Cd in the walls of AAA coexisting with iliac artery aneurysms may suggest an impact on the accumulation of this toxic element and greater damage of the iliac artery wall [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we found disturbed proportions between Cu and Pb in TAA and Zn and Pb in both types of aneurysm, while concentration of Cd is similar to normal aortas in both types of aneurysm. Other studies have shown that the elevated levels of Cd in the walls of AAA coexisting with iliac artery aneurysms may suggest an impact on the accumulation of this toxic element and greater damage of the iliac artery wall [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only few studies have been conducted to evaluate the oxidative stress status of AAA patients. Some studies reported imbalance of mineral components in patients with aneurysms [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, an association with a lower content of Ni as well as a significantly higher content of Cd was demonstrated. The levels of remaining trace elements like Cu, Zn, Mn, Mg, and Ca were detected at similar concentrations [ 105 ]. The authors of this study linked the higher Cd concentrations to an increased exposure to tobacco smoke [ 68 , 106 ].…”
Section: The Role Of Trace Elements In Selected Cardiovascular Diseasesmentioning
confidence: 99%
“…However, the variation of the Ni contents in this study were found not to be statistically relevant. This was most likely due to the small size of the study group, as claimed by the authors, since the content of trace elements was assessed in samples of AAA walls harvested intraoperatively in only 19 consecutive patients [ 105 ].…”
Section: The Role Of Trace Elements In Selected Cardiovascular Diseasesmentioning
confidence: 99%